Primera aproximación al impacto social y económico de la coca-cocaína en el Departamento de Tarija - Carvajal A., Paola A. (Drogas - investigación para el debate, 1993)
"Commissioned report on the increased illegal narcotrafficking activity in the city of Yacuiba on Bolivia/Argentina border provides a general analysis, neglecting much of the related social sciences literature. Does provide interesting figures for a geographic area about which little has been written"--Handbook of Latin American Studies, v. 57